x+3=6(8-3x)-7

Simple and best practice solution for x+3=6(8-3x)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3=6(8-3x)-7 equation:


Simplifying
x + 3 = 6(8 + -3x) + -7

Reorder the terms:
3 + x = 6(8 + -3x) + -7
3 + x = (8 * 6 + -3x * 6) + -7
3 + x = (48 + -18x) + -7

Reorder the terms:
3 + x = 48 + -7 + -18x

Combine like terms: 48 + -7 = 41
3 + x = 41 + -18x

Solving
3 + x = 41 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
3 + x + 18x = 41 + -18x + 18x

Combine like terms: x + 18x = 19x
3 + 19x = 41 + -18x + 18x

Combine like terms: -18x + 18x = 0
3 + 19x = 41 + 0
3 + 19x = 41

Add '-3' to each side of the equation.
3 + -3 + 19x = 41 + -3

Combine like terms: 3 + -3 = 0
0 + 19x = 41 + -3
19x = 41 + -3

Combine like terms: 41 + -3 = 38
19x = 38

Divide each side by '19'.
x = 2

Simplifying
x = 2

See similar equations:

| 7150=6.25*r*5 | | A=1/2*bh | | 5x+3y=40 | | -6a+28=-(2a-8) | | 9x^2+18x+17=0 | | 5c^3+30c-35c=0 | | 3(-8n-2)=-2n+16 | | 24x-4x^2=0 | | 3y-9=6y+3 | | 5x+5(2+6x)=10+3x | | (6+y)(3y+7)=0 | | (2x)lnx+x=0 | | -15-5r=5(1+3r) | | (5v-7)(3-v)=0 | | 4x+4=5x+10 | | (2n-3)(n+4)=0 | | 6c-6-2c-5-3c+7= | | 8+(x+5)= | | x^3-10x^2+13x+74=0 | | 5b+3(3b+4)=-24+2b | | x*2-x=20 | | v=(50-2x)(50-2x)(x) | | y=5*cos*2x+11 | | (5z+6)(4-z)=0 | | q-1=5q+3q-8 | | 0.16=-0.4+0.7x | | 8.5+3.4= | | (4z+7)(5+z)=0 | | 1.2=-1.4+20x | | -9x+4y=7 | | 5x-y=14.9 | | 5x+7=-6+2x+19 |

Equations solver categories